The impact of emotional self-regulation on performative success for professional fighters - Kwamanakweenda, J.; Pino, J.; van Hauwermeiren, O.; Peacock, C.; Tartar, J.; Cuc, A. (Research Directs in Psychology and Behavior, 2022)
Introduction: Emotional self-regulation has been determined to be an important factor regarding outcomes for athletes. Previous research has examined strategies athletes use to regulate their emotions and their motivations for doing so. However, little research has examined how professional fighters utilize emotional self-regulation strategies and their impact on performance. Fighters have been perceived as aggressive and impulsive; hence it is important to examine how they regulate their emotions. The present study investigates the association of emotional self-regulation in professional fighters versus college-aged male nonfighters. The study also evaluates the relationship between emotional self-regulation and winning percentages in professional fighters.